Conformational analysis and global warming potentials of 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol from absorption spectroscopy. (December 2017) - Godin, Paul J.; Le Bris, Karine; Strong, Kimberly
Abstract: Absorption cross-sections of 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol (HFIP) were derived from Fourier transform infrared spectra recorded from 530 to 3400 cm − 1 with a resolution of 0.1 cm − 1 over a temperature range of 300–362 K. These results were compared to previously published experimental measurements made at room temperature and to a theoretical spectrum from density functional theory (DFT) calculations. Good agreement is found between the experimentally derived results, DFT calculations, and previously published data. The only temperature dependence observed was in the amplitude of some of the absorption peaks due to the changing ratio of the stable conformations of HFIP. This temperature dependence does not result in a significant trend in integrated band strength as a function of temperature. The average value for integrated band strength is found to be (2.649 ± 0.065)x10 − 16 cm molecule − 1 for HFIP over the spectral range of 595 to 3010 cm − 1 . Radiative efficiency (RE) and the global warming potential (GWP) for HFIP were also derived. A RE of 0.293 ± 0.059 Wm − 2 ppbv − 1 is derived, which leads to a GWP100 of 188 in the range of 530 to 3000 cm − 1 . The DFT calculation is linearly adjusted to match the experimental spectrum. Using this adjusted DFT spectrum to expand the range below 530 to 0 cm − 1, increases the RE to 0.317 ± 0.063 Wm − 2 ppbv − 1 and the GWP100 to 203. Highlights: Cross-sections of 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol (HFIP) were measured from 530 to 3400 cm-1 for a temperature range of 300–362 K. Good agreement between new results, prior data, and density functional theory (DFT). HFIP is found to exist in a ratio of 78% trans and 22% gauche conformations at room temperature. Radiative efficiency and global warming potential are calculated using a combination of DFT and experimental spectra to obtain a wider spectral range. The inclusion of a wider spectral range increases the RE and GWP values above thier current accepted values.